BIRB796, the Inhibitor of p38 Mitogen-Activated Protein Kinase, Enhances the Efficacy of Chemotherapeutic Agents in ABCB1 Overexpression Cells - He, Dan; Zhao, Xiao-qin; Chen, Xing-gui; Fang, Yi; Singh, Satyakam; Talele, Tanaji T.; Qiu, Hui-juan; Liang, Yong-ju; Wang, Xiao-kun; Zhang, Guo-qing; Chen, Zhe-sheng; Fu, Li-wu (PLOS ONE, 2013)
ATP-binding-cassette family membrane proteins play an important role in multidrug resistance. In this study, we investigated BIRB796, an orally active inhibitor of p38 mitogen-activated protein kinase, reversed MDR induced by ABCB1, ABCG2 and ABCC1. Our results showed that BIRB796 could reverse ABCB1-mediated MDR in both the drug selected and transfected ABCB1-overexpressing cell models, but did not enhance the efficacy of substrate-chemotherapeutical agents in ABCC1 or ABCG2 overexpression cells and their parental sensitive cells. Furthermore, BIRB796 increased the intracellular accumulation of the ABCB1 substrates, such as rhodamine 123 and doxorubicin. Moreover, BIRB796 bidirectionally mediated the ATPase activity of ABCB1, stimulating at low concentration, inhibiting at high concentration. However, BIRB796 did not alter the expression of ABCB1 both at protein and mRNA level. The down-regulation of p38 by siRNA neither affected the expression of ABCB1 nor the cytotoxic effect of paclitaxel on KBV200. The binding model of BIRB796 within the large cavity of the transmembrane region of ABCB1 may form the basis for future lead optimization studies. Importantly, BIRB796 also enhanced the effect of paclitaxel on the inhibition of growth of the ABCB1-overexpressing KBV200 cell xenografts in nude mice. Overall, we conclude that BIRB796 reverses ABCB1-mediated MDR by directly inhibiting its transport function. These findings may be useful for cancer combinational therapy with BIRB796 in the clinic.